Use of Cefoxitin, New Cephalosporin-Like Antibiotic, in the Treatment of Aerobic and Anaerobic Infections - Nair, S. Ramachandran (1978)
Forty-two patients were treated with intravenous cefoxitin, a new cephamycin antibiotic. These patients had postoperative abdominal sepsis (26), intrathoracic infections (6), urinary tract infections (5), gram-negative bacterial meningitis (2), septic arthritis (1), epidural abscess (1) and isolated septicemia (1). The antibacterial spectrum of cefoxitin was found to be one which included all gram-positive organisms except enterococci, most gram-negative organisms except Pseudomonas aeruginosa, and almost all of the important anaerobic organisms. The only five treatment failures included one patient with empyema and one with septic arthritis, both caused by Serratia marcescens, initially only moderately susceptible to cefoxitin, which subsequently developed increased resistance, two patients with contaminated intravenous catheters, and one patient with epidural abscess and cerebritis, who was treated late in the course. There was one serious clinical superinfection with P. aeruginosa. The drug levels noted in the pus and joint fluid were half to two-thirds of the simultaneous serum level. In inflamed meninges, up to 30% of the serum level was noted in the cerebrospinal fluid, and as the process resolved, 10 to 15% was noted. Toxicity of cefoxitin was mild and constituted skin rash in three patients (7%) and phlebitis in eight (19%).